FMCG Supply Chain Optimization through Vendor Managed Inventory (VMI) : Case Study of Anheuser-Busch InBev - Gaifullin, Timur (2024)
The thesis examines the potential of Vendor Managed Inventory in optimizing supply chain performance within the Fast-Moving Consumer Goods sector. The evaluation is based on the case study of global beer producer Anheuser-Busch InBev. The research aims to evaluate how effective VMI in increasing supply chain efficiency, compare VMI with Customer Managed Inventory (CMI) and estimate how reasonable is the transition between the two models when trying to achieve better operational results. The case study demonstrates that VMI can improve supply chain performance by increasing customer satisfaction, reducing waste and achieving superior KPI results. The comparative analysis highlights that VMI requires higher initial investments, advanced technological infrastructure and strong collaboration between supplier and customer, however, it offers greater long-term benefits compared to CMI. Additionally, the thesis stresses the importance of considering factors specific to the market and industry when deciding between VMI and CMI.